2007
DOI: 10.1086/519392
|View full text |Cite
|
Sign up to set email alerts
|

West Nile Virus Neutralization by US Plasma–Derived Immunoglobulin Products

Abstract: The 1999 introduction of West Nile virus (WNV) into the United States has resulted in the largest epidemic of arboviral illness in the Western Hemisphere, with an estimated 2.5 million cases of mostly asymptomatic human infections since then. As a consequence, an increasing occurrence of WNV antibodies in plasma collected in the United States, and thus in intravenous immunoglobulin (IVIG) products, can be expected. Using an in vitro assay to investigate antibody function, rather then presence, almost 1000-fold… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
61
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(61 citation statements)
references
References 22 publications
0
61
0
Order By: Relevance
“…The TBEV neutralisation titres of IVIG have not changed over time, and thus the increase in WNV neutralisation titres is most likely a true reflection of increased virus circulation. Using the same, fully validated assay, reconvalescent sera from human WNV cases in North America have earlier been shown to have a mean NT 50 of 208 [41], 120-fold higher than the increase now observed. This would indicate past WNV exposure of just under 1% of the population of Austria, Germany and the Czech Republic.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…The TBEV neutralisation titres of IVIG have not changed over time, and thus the increase in WNV neutralisation titres is most likely a true reflection of increased virus circulation. Using the same, fully validated assay, reconvalescent sera from human WNV cases in North America have earlier been shown to have a mean NT 50 of 208 [41], 120-fold higher than the increase now observed. This would indicate past WNV exposure of just under 1% of the population of Austria, Germany and the Czech Republic.…”
Section: Discussionmentioning
confidence: 79%
“…As the detection of antibodies to the WNV NS1 protein is serotype-specific, a possible contribution of antibodies against dengue virus can be excluded. The theoretical possibility of a contribution of neutralising antibodies to Usutu virus (USUV) [39], a virus that belongs to the same serocomplex as WNV, was not evaluated in vitro, as even the highest USUV activity in Austria as observed during the summer of 2003 [40] had no impact on the WNVspecific neutralisation titres in IVIG lots [41]. Moreover, despite a comprehensive surveillance programme for dead birds and mosquitoes in Austria [42], where around 45% of the plasma is collected for production of the IVIG lots tested in this study, no evidence of human exposure to USUV could be found [43], which makes a significant contribution of USUV antibodies to WNV neutralisation titres determined in the present study unlikely.…”
Section: Discussionmentioning
confidence: 99%
“…Human serum obtained from WNV convalescent patients (WNV-IVIG) was provided by the American Red Cross, as described previously (Planitzer et al, 2007). IVIG (Carimune NF) was obtained from CSL Behring.…”
Section: Methodsmentioning
confidence: 99%
“…When a virus or microbial agent is expanding its geographical range, exposure of the formerly naïve population to this novel agent is reflected in the Ab content of IVIG. This was demonstrated, e.g., for US-IVIG after the introduction of WNV into the United States in 1999 (4,25,31) and recently also for EU-IVIG, where increasing WNV-neutralizing Ab titers were detected in EU-IVIG lots manufactured after 2009, even though no human WNV infections have yet been reported from the countries in which the plasma was sourced (31).To further increase the understanding of the geographical difference in IVIG Ab content, we determined the neutralizing Ab titers of IVIG preparations for tick-borne encephalitis virus (TBEV). This member of the Flaviviridae, for which three subtypes (European, Siberian, and Far Eastern) are distinguished, may cause tick-borne encephalitis (TBE), a potentially serious neurological disease with high fever and encephalitis (33), while 70 to 95% of human infections in regions in which the virus is endemic are either subclinical or totally asymptomatic (12).…”
mentioning
confidence: 88%
“…When a virus or microbial agent is expanding its geographical range, exposure of the formerly naïve population to this novel agent is reflected in the Ab content of IVIG. This was demonstrated, e.g., for US-IVIG after the introduction of WNV into the United States in 1999 (4,25,31) and recently also for EU-IVIG, where increasing WNV-neutralizing Ab titers were detected in EU-IVIG lots manufactured after 2009, even though no human WNV infections have yet been reported from the countries in which the plasma was sourced (31).…”
mentioning
confidence: 92%